Evaluation of an Al-Ce alloy for laser additive manufacturing. (March 2017) - Plotkowski, A.; Rios, O.; Sridharan, N.; Sims, Z.; Unocic, K.; Ott, R.T.; Dehoff, R.R.; Babu, S.S.
Abstract: This study focuses on the development of a design methodology for alloys in AM, using a newly developed Al-Ce alloy as an initial case study. To evaluate the candidacy of this system for directed energy deposition processes, single-line laser melts were made on cast Al-12Ce plates using three different beam velocities (100, 200, and 300 mm/min). The microstructure was evaluated in the as-melted and heat treated conditions (24 h at 300 °C). An extremely fine microstructure was observed within the melt pools, evolving from eutectic at the outer solid-liquid boundaries to a primary Al FCC dendritic/cellular structure nearer the melt-pool centerline. The observed microstructures were rationalized through the construction of a microstructure selection map for the Al-Ce binary system, which will be used to enable future alloy design. Interestingly, the heat treated samples exhibited no microstructural coarsening. Graphical abstract: Image